IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK AUTIS DI SEKOLAH LUAR BIASA NEGERI CIAMIS - Reni Rahmawati; Anis Husni Firdaus; Selamet Selamet (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2018)
This study aims to find out in depth the learning process of Islamic Religious Education in children with autism and the problems faced when learning Islamic Religious Education takes place in the Ciamis State Special School (SLB). The objectives to be achieved from this study are to describe the learning outcomes of Islamic Religious Education in children with autism in the Ciamis Extraordinary School, namely as follows: 1) to find out the planning of Islamic Religious Education learning for autistic children in SLB Negeri Ciamis; 2) to find out the implementation of Islamic Religious Education learning for autistic children in SLB Negeri Ciamis; 3) to find out the evaluation of Islamic Religious Education learning for autistic children in SLB Negeri Ciamis. This study uses a qualitative approach with qualitative descriptive methods. Data collection uses observation, interview, and documentation techniques. This research was conducted from March to May. The data source is students with special needs for autism at the Ciamis Extraordinary School, while for supplementary data researchers conducted interviews and documentation studies. Then after the data collected continues with data reduction, presenting data, verifying data, and drawing conclusions. The results showed that: (1) Learning planning includes all aspects of supporting the implementation of the learning process. The learning process of PAI in autistic children in the school of the Ciamis Extraordinary School follows the 2013 curriculum with teacher modifications. The material presented is emphasized on practical material using various methods in accordance with the needs of students. The learning process is guided by the educational component, namely: objectives, educators, students, curriculum, material, methods and evaluation, because all of these components are used as benchmarks in adjusting the child's abilities, so that the desired learning objectives can be achieved. At the learning planning stage the teacher also prepares a learning kit, namely syllabus and lesson plans; (2) The implementation of PAI learning in autistic children places more emphasis on character education / morals, the learning methods used are varied, adapted to the needs of students. The implementation of PAI learning includes preliminary or apperception activities, core activities, and closing activities. Allocation of implementation time is 2 hours of study (2x35 minutes) and is carried out every Thursday at 07.30 until 08.40 WIB; (3) Evaluations carried out in SLB Negeri Ciamis are carried out in three activities namely case evaluation, semester program evaluation and follow-up. The PAI learning results show that autistic children experience development / progress in carrying out religious rituals, and in living behavior as the demands of their religion. This is shown as ablution, prayer, daily prayers and others. Assessment standards and minimum completeness criteria scores (KKM) are set by the school